Direct effects of remote ischemic preconditioning on post-exercise-induced changes in kynurenine metabolism - Brzezińska, Paulina; Mieszkowski, Jan; Stankiewicz, Błażej; Kowalik, Tomasz; Reczkowicz, Joanna; Niespodziński, Bartłomiej; Durzyńska, Aleksandra; Kowalski, Konrad; Borkowska, Andżelika; Antosiewicz, Jędrzej; Kochanowicz, Andrzej (Frontiers in Physiology, 2024)
PurposeTryptophan (TRP) degradation through the kynurenine pathway is responsible for converting 95% of free TRP into kynurenines, which modulate skeletal muscle bioenergetics, immune and central nervous system activity. Therefore, changes in the kynurenines during exercise have been widely studied but not in the context of the effects of remote ischemic preconditioning (RIPC). In this study, we analyzed the effect of 14-day RIPC training on kynurenines and TRP in runners after running intervals of 20 × 400 m.MethodsIn this study, 27 semi-professional long-distance runners were assigned to two groups: a RIPC group performing 14 days of RIPC training (n = 12), and a placebo group, SHAM (n = 15). Blood was collected for analysis before, immediately after, and at 6 h and 24 h after the run.ResultsAfter the 14-day RIPC/SHAM intervention, post hoc analysis showed a significantly lower concentration of XANA and kynurenic acid to kynurenine ratio (KYNA/KYN) in the RIPC group than in the SHAM group immediately after the running test. Conversely, the decrease in serum TRP levels was higher in the RIPC population.ConclusionRIPC modulates post-exercise changes in XANA and TRP levels, which can affect brain health, yet further research is needed.